P805 Selnoflast, a potent NLRP3 inhibitor - results from a phase 1b experimental medicine study in patients with Ulcerative Colitis. (30th January 2023) - Klughammer, B; Piali, L; Nica, A C; Nagel, S; Bailey, L; Jochum, C; Ignatenko, S; Bläuer, A; Danilin, S; Gulati, P; Hayward, J; Scepanovic, P; et al.
Abstract: Background: The Nucleotide-binding oligomerization domain, leucine rich repeat and pyrin domain containing 3 (NLRP3) inflammasome is a driver of caspase 1-dependent release of IL-1β and IL-18 and has been identified as a potential drug target for ulcerative colitis (UC) (Tourkochristou et al. 2019). Selnoflast (RO7486967) is an orally active, potent, selective, and reversible small molecule NLRP3 inhibitor. To assess whether NLRP3 is a driver of inflammation and more specifically of IL-1β production and signaling in UC, we performed a Phase 1b study (BP43099) with selnoflast in patients with UC. Methods: A randomized, placebo-controlled, double blind study assessed safety, tolerability, PK and PD of selnoflast in patients with active, moderate to severe UC. 19 patients were recruited: 6 were treated with placebo and 13 were treated with 450 mg selnoflast QD for 7 days. Stool and blood samples were taken at baseline, during and at the end of treatment. Sigmoidal tissue samples were taken at baseline and at the end of treatment. Adverse events were assessed throughout the study. https://www.isrctn.com/ISRCTN16847938 Results: Selnoflast was well tolerated in all patients, with mainly mild AEs. No serious or severe AEs were reported. Plasma PK was in line with PK data from previous studies in healthy subjects. In addition, selnoflast demonstrated a good distribution in sigmoidal tissue in all treated patients. The gene signature of 8 genes (i.e. CXCL1, CXCL2, CXCL3, CXCL5, CXCL6, CCL2, IL-6, TNFAIP6) downstream of IL-1β, known to be responsive to IL-1β stimulation across different cell types and differentially expressed in colonic biopsies (UC vs healthy), was assessed and showed on average a slight decrease from baseline after treatment with selnoflast compared to placebo (log2 fold change mean (sd) = -1.14 (1.8) and +0.38 (3.26) respectively, t-test p-value = 0.206) in sigmoidal tissue biopsies. Single-cell RNA sequencing showed minimal differences between the two treatment arms. Conclusion: Selnoflast was well tolerated and achieved the plasma and tissue exposure predicted to inhibit NLRP3. Expression of IL-1β gene signature in sigmoidal tissue biopsies, single-cell RNA sequencing and additional biomarker analyses showed no robust differences between the two treatment arms, suggesting that targeting the NLRP3 inflammasome with selnoflast may be of limited therapeutic benefit to reduce inflammation in UC. Tourkochristou E, Aggeletopoulou I, Konstantakis C, Triantos C. Role of NLRP3 inflammasome in inflammatory bowel diseases. World J Gastroenterol. 2019